Pendidikan Kritis Menurut Ivan Illich - Firman Amir (Jurnal Ilmiah Wahana Pendidikan, 2022)
Ivan Illich did not advocate abolishing schools, but disestablishment, or do not regard schools as superior, rigid, authoritarian institutions, and tend to force people to just follow their policies. He is dissatisfied with schools whose operations are funded by the community through taxes, but are less accessible to the community, as a result of various regulations that are difficult for the community to enter. According to Illich, the objective conditions and educational situation that took place in Latin America at that time were not able to answer and resolve all kinds of social problems faced by students in his era. The school only encouraged and made students feel alienated from the social life they faced at that time, the school was likened to an institution to force all children to climb the educational ladder which had no end and was not qualified to give birth to the potential of students. The compulsory learning system in schools kills the free will and creativity of many people for independent learning to increase their creative potential in life, knowledge is carried out like a commodity, packaged, and then sold to students at very high prices